2021
DOI: 10.1080/09669582.2021.1948553
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing nature-based science tourism: a case study of Seili Island, Finland

Abstract: Nature-based tourism has been widely addressed, yet research on nature-based science tourism, founded on science, scientific knowledge, and/or engagement in scientific research, is still scarce. Drawing on tourist motivation, nature-based tourism, special interest tourism, and science tourism, a novel theoretical conceptualization of nature-based science tourism was developed. The framework identified three categories of science tourism with intensifying levels of tourists' interest in scientific knowledge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
0
13
0
2
Order By: Relevance
“…Likewise, Rivera (2015) refers to active tourism as an emerging segment of strategic interest for some destinations in Spain, and Haegeli (2016) referred to Kuenzi and McNeely's statement about nature-based tourism being the "fastest growing sector of the global tourism industry". Despite this steady growth of the outdoor recreation industry and related businesses, Haegeli (2016) also acknowledged that academic research on this area has not evolved at the same pace; similar statement is made by Raikkonen et al (2021). Durán (2015) recalled the high number of authors who question if the importance given to research on tourism in Spain can be compared with the importance that the sector has; and Vargas (2011) considered that research on tourism has a short academic tradition.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Likewise, Rivera (2015) refers to active tourism as an emerging segment of strategic interest for some destinations in Spain, and Haegeli (2016) referred to Kuenzi and McNeely's statement about nature-based tourism being the "fastest growing sector of the global tourism industry". Despite this steady growth of the outdoor recreation industry and related businesses, Haegeli (2016) also acknowledged that academic research on this area has not evolved at the same pace; similar statement is made by Raikkonen et al (2021). Durán (2015) recalled the high number of authors who question if the importance given to research on tourism in Spain can be compared with the importance that the sector has; and Vargas (2011) considered that research on tourism has a short academic tradition.…”
Section: Introductionmentioning
confidence: 93%
“…The concerns on the relationship between tourism and sustainable development (Sharpley, 2020; Fosse et al, 2017;Simo-Kengne, 2021), the necessity of developing academic research on nature-based tourism (Haegeli, 2016;Raikkonen, 2021) and the current significance of the SDG, served as the foundation for the following research question: To what extent can active tourism activities make contributions to the economic, environmental, social, cultural and governance dimensions of sustainability?…”
Section: Introductionmentioning
confidence: 99%
“…However, there are diverse opinions suggesting that science tourism can be categorized into visiting, listening to explanations, and hands-on participation ( [34] cited from Ereshko F. I., 2006). For instance, Räikkönen et al conducted a study on the motivations of tourists for natural science tourism in Seili Island, Finland revealed that the primary motivation behind science tourism is learning purposes [35] .…”
Section: Reviewmentioning
confidence: 99%
“…A significant component of global tourism is nature-based tourism [32]. For a very long time, natural places and attractions have drawn tourists who enjoy being outside and engaging in outdoor activities [33,34]. Increasingly, people around the world are drawn to nature-based tourism and leisure that involves being outside and embracing it [35,36].…”
Section: Nature-based Tourismmentioning
confidence: 99%